Optimizing Student Management to Improve Student Discipline in Senior High Schools - Usep Purkon Ramdani (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2026)
This study is motivated by the decline in student discipline at MA YPK Cijulang during the 2021–2025 period, as indicated by increasing tardiness, unexcused absences, and decreasing adherence to school rules. The main objective of this research is to analyze the optimization of student management in improving student discipline and to identify its supporting and inhibiting factors. This research employs a qualitative approach with descriptive methods. Data collection techniques include interviews, observations, and documentation, with research subjects consisting of the school principal, guidance counselors, vice principals, and students. This study is limited to the context of MA YPK Cijulang and does not directly examine external factors such as family or social environments. The implication is that the findings can serve as a reference for other Islamic-based madrasahs to develop student management strategies grounded in spiritual values. The study reveals that student management is optimized through four functions: planning, organizing, implementing, and supervising. Strategies such as routine religious activities, active student involvement in OSIS and extracurriculars, and guidance counseling programs have proven effective in fostering a culture of discipline. The main obstacles include limited facilities and negative perceptions of the counseling room. These findings align with Mulyasa's management theory and Maslow's hierarchy of needs, as well as Islamic values from QS. At-Tahrim: 6 and QS. As-Saff: 4, reinforcing the moral foundation of student character building. This research offers a holistic approach to student management based on Islamic values, a perspective that has been scarcely explored in prior studies. Its novelty lies in integrating educational management theory, psychological needs theory, and Islamic values in shaping student discipline.